Oszacowanie wpływu rozpraszania światła przez atmosferę na pomiar reflektancji wykonywany podczas lotów fotogrametrycznych na niskim pułapie nad terenami leśnymi - Mazur, Anna; Kacprzak, Mariusz; Kotlarz, Jan; Kubiak, Katarzyna; Skocki, Krzysztof (Leśne Prace Badawcze, 2018)
In this article, we describe methods for the correction of multispectral aerial images by accounting for atmospheric interference. We also summarize the first correction results for images acquired at flight altitudes and evaluate the suitability of selected methods for the atmospheric correction of these images. Furthermore, processes and phenomena occurring in the atmosphere that potentially affect image quality and interfere with the electromagnetic radiation registered by the imaging sensors are discussed as well. The purpose of atmospheric correction is to reduce or eliminate atmospheric interference during multispectral image processing. Here we present methodology for image correction based on data gathered at various altitudes during the autumn flights conducted as part of the HESOFF project.